Design and construction Optically Gas Laser (Baghdad Science Journal, 2013)
In this work the design and construction of a flash photolysis pulsed HCl laser was presented. The parameters of the pumping source and discharge current density was obtained, which sufficient to shift the flash lamp spectrum towards uv portion of spectrum. The maximum pulse laser energy parameters was measured. Total pressure and ratio of active gases to optimized the output pulse energy were measured , where at 125 mbar of total pressure and 1:7:14 Cl2:H2: He ratio, the laser energy was measured to be 200 mJ at pumping four flash lamps energy in the order of 6400J .The resonator consists of copper a near hemispherical mirror with the radius of curvature 3m coated by gold and reflectivity 98%,the output coupler sapphire mirror of 63% reflectivity . Total efficiency of the system was measured to be 0.0125% .